2023
DOI: 10.3390/healthcare11060908
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Robson Classification in Greece: A Retrospective Cross-Sectional Study

Abstract: Cesarean sections have become the most commonly performed operations around the world. The World Health Organization recommended the use of the Robson classification system as a universal standard to establish a joint control system in healthcare facilities. The aim of this study was to implement the Robson classification for the first time in Greece to identify trends in cesarean births and examine the groups of women who are the main contributors to the increasing rates. Moreover, the indicators for cesarean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Our earlier study showed that cephalopelvic disproportion and previous cesarean section are the most frequent indications for a cesarean section [25]. Several studies have associated high cesarean section rates with non-clinical factors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our earlier study showed that cephalopelvic disproportion and previous cesarean section are the most frequent indications for a cesarean section [25]. Several studies have associated high cesarean section rates with non-clinical factors.…”
Section: Discussionmentioning
confidence: 95%
“…The present study is part of a wider research protocol on the implementation of the Robson classification in the Greek classification setting. The methods of the research study have been previously published and are summarized here as follows [25]. This is a single-center retrospective study conducted between January and December 2019.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Classification of CD clinical factors is important as it allows for an understanding and comparison of different classification rates and audit results (Table 2). [9][10][11][12] Trial of labor after caesarean delivery (TOLAC) and vaginal delivery after caesarean delivery (VBAC) 3,4 are similar terms for the option of waiting for the onset of spontaneous labor and the opportunity for a possible vaginal delivery, following a previous CD delivery. Important counselling issues are related to the indication for the previous caesarean delivery, the patient motivation for a vaginal delivery, the limited opportunity for oxytocin use in labor and the 1% risk for uterine rupture during labor, with maternal and neonatal morbidity and possible neonatal mortality.…”
Section: Counselling Overview For the Four Obstetrical Surgery Optionsmentioning
confidence: 99%
“…The ten Robson categories (Table 2) are mutually exclusive, totally inclusive, and can be applied prospectively, with each pregnant person that is admitted for delivery can be classified immediately, using a few variables that are generally routinely recorded. [9][10][11][12]50,51 The Robson classification system helps with institution-specific monitoring and auditing but offers a standardised comparison method that can be used between institutions, countries, and timepoints. 50 The Robson classification system (Table 2) has had some modifications to the original Robson groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation